2009
DOI: 10.1063/1.3263918
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular dynamics simulation of photoisomerization in azobenzene in the nπ∗ state

Abstract: Photoisomerization mechanism of azobenzene in the lowest excited state S 1 ͑n ‫ء‬ ͒ is investigated by ab initio molecular dynamics ͑AIMD͒ simulation with the RATTLE algorithm, based on the state-averaged complete active space self-consistent field method. AIMD simulations show that cis to trans isomerization occurs via two-step rotation mechanism, accompanying rotations of the central NN part and two phenyl rings, and this process can be classified into two types, namely, clockwise and counterclockwise rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
131
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(145 citation statements)
references
References 39 publications
(72 reference statements)
13
131
1
Order By: Relevance
“…This finding can explain, why in dynamics simulations the isomerization occurs through a rotation of the -N=N-fragment rather than a true torsion along the N-N bond. 47,55 Finally, we summarize significant results from the present calculations. First, we should mention that we employ the CASPT2 method in determinations of geometrical structures, vibrational frequencies, and reaction pathways.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…This finding can explain, why in dynamics simulations the isomerization occurs through a rotation of the -N=N-fragment rather than a true torsion along the N-N bond. 47,55 Finally, we summarize significant results from the present calculations. First, we should mention that we employ the CASPT2 method in determinations of geometrical structures, vibrational frequencies, and reaction pathways.…”
Section: Resultsmentioning
confidence: 80%
“…27,28,30,31,42,58 On-the-fly dynamics simulations were also performed for the photoisomerization of azobenzene on the basis of semiempirical molecular orbital calculations with the surface hopping method 29,33,55,59,61 and with the multiple spawning method. 32 Recently, ab initio molecular dynamics (AIMD) simulations at the CASSCF level 26,47,54,57 and Car-Parrinello molecular dynamics simulations 34,45,49,50 were also performed for the photoisomerization of azobenzene in nπ * excitation. In our surface hopping AIMD simulation 47 at the state-averaged CASSCF (SA-CASSCF) level, it was shown that cis to trans isomerization in nπ * excitation occurs via two-step rotation mechanism, accompanying rotations of the central NN part and two phenyl rings, and this process can be classified into two types with respect to the orientation of the rotation, namely, clockwise and counterclockwise rotation pathways; the calculated quantum yields and lifetime in the excited states are in very good agreement with the corresponding experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the viewpoint of fundamental photochemistry, particularly, trans-cis photoisomerization mechanism and excited state decay dynamics of azobenzene are still a long standing issue to be much debated between theoretical calculations and experiments because of very fast isomerization process. [5][6][7][8][9][10][11] Recent ultrafast time-resolved spectroscopic results from probing short-lived azobenzene excited states propose that the isomerization pathways are rather complicated processes involving multiple relaxation channels. 12 In principle, azobenzene undergoes trans-cis photoisomerization by the excitation of the S 1 (n → π*) and the S 2 (π → π*) states in the UV and visible region.…”
mentioning
confidence: 99%